K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

19 tháng 10 2018

a) \(x^2-9x+14\)

\(=x^2-2x-7x+14\)

\(=x\left(x-2\right)-7\left(x-2\right)\)

\(=\left(x-2\right)\left(x-7\right)\)

b) \(x^2+17x-18\)

\(=x^2+18x-x-18\)

\(=x\left(x+18\right)-\left(x+18\right)\)

\(=\left(x+18\right)\left(x-1\right)\)

c) \(2x^2-7x+3\)

\(=2x^2-x-6x+3\)

\(=x\left(2x-1\right)-3\left(2x-1\right)\)

\(=\left(2x-1\right)\left(x-3\right)\)

d) \(x^2-25x+144\)

\(=x^2-9x-16x+144\)

\(=x\left(x-9\right)-15\left(x-9\right)\)

\(=\left(x-9\right)\left(x-15\right)\)

3 tháng 7 2016

a) =x3-2x2+x2-2x+x-2

=x2(x-2)+x(x-2)+(x-2)

=(x-2)(x2+x+1)

3 tháng 7 2016

\(a.=x^3-2x^2+x^2-2x+x-2=x^2\left(x-2\right)+x\left(x-2\right)+\left(x-2\right)=\left(x-2\right)\left(x^2+x+2\right)\)

b.\(=2x^3+x^2-2x^2-x-2x-1=x^2\left(2x+1\right)-x\left(2x-1\right)-\left(2x-1\right)\)\(=\left(2x-1\right)\left(x^2-x-1\right)\)

c.\(3x^3-x^2+6x^2-2x-12x+4=x^2\left(3x-1\right)+2x\left(3x-1\right)-4\left(3x-1\right)\)\(=\left(3x-1\right)\left(x^2+2x-4\right)\)

d.\(3x^3-x^2-6x^2+2x+15x-5=x^2\left(3x-1\right)-2x\left(3x-1\right)+5\left(3x-1\right)\)\(=\left(3x-1\right)\left(x^2-2x+5\right)\) 

t i c k cho mình nha

4 tháng 9 2018

\(3x^3-7x^2+17x-5\)

\(=3x^3-6x^2-x^2+15x+2x-5\)

\(=\left(-6x^2+2x\right)+\left(3x^3+15x\right)-\left(x^2+5\right)\)

\(=-2x\left(3x-1\right)+3x\left(x^2+5\right)-\left(x^2+5\right)\)

\(=-2x\left(3x-1\right)+\left(x^2+5\right)\left(3x-1\right)\)

\(=\left(3x-1\right)\left(-2x+x^2+5\right)\)

30 tháng 8 2019

2x4 -19x3+ 2002x2 -9779x+11670

= 2x^4 -6x^3-13x^3+39x^2+1963x^2-5889x-3890x+11670

= 2x^3(x-3)-13x^2(x-3)+1963x(x-3)-3890(x-3)

=(x-3)(2x^3-13x^2+1963x-3890)

=(x-3)(2x^3-4x^2-9x^2+18x+1945x-3890)

=(x-3)(2x^2(x-2)-9x(x-2)+1945(x-2))

=(x-3)(x-2)(2x^2-9x+1945)

21 tháng 10 2016

Nhầm (3x - 1)(x2 - 2x + 5) mới đúng nha

21 tháng 10 2016

3x3 - 7x2 + 17x - 5x = (3x3 - x2) + (- 6x2 + 2x) + (15x - 5)

= (3x - 1)(x2 - 6x + 5)

12 tháng 7 2017

\(3x^3-7x^2+17x-5.\)

\(=3x^3-x^2-6x^2+2x-15x+5\)

\(=\left(3x^3-x^2\right)-\left(6x^2-2x\right)-\left(15x-5\right)\)

\(=x^2\left(3x-1\right)-2x\left(3x-1\right)-5\left(3x-1\right)\)
\(=\left(3x-1\right)\left(x^2-2x-5\right)\)